Stacking stability and sliding mechanism in weakly bonded 2D transition metal carbides by van der Waals force. Issue 88 (11th December 2017) - Zhang, H.; Fu, Z. H.; Legut, D.; Germann, T. C.; Zhang, R. F.
Abstract : The stability of the stacked two-dimensional (2D) transition metal carbides and their interlayered friction in different configurations are comparatively studied by means of density functional theory (DFT). Abstract : The stability of the stacked two-dimensional (2D) transition metal carbides and their interlayered friction in different configurations are comparatively studied by means of density functional theory (DFT). At equilibrium, a larger interlayer distance corresponds to a smaller binding energy, suggesting an easier sliding between them. The oxygen-functionalized M2 CO2 possesses much lower sliding resistance than the bare ones due to the strong metallic interactions between the stacked M2 C layers. Compared to the parallel stacking order of M2 CO2 -I, the mirror stacked M2 CO2 -II possesses better lubricant properties. At strained states, normal compression substantially enhances the sliding barrier owing to more charges transferring from the M to O atom. Furthermore, the in-plane biaxial strain may effectively hinder the interlayer sliding, while the uniaxial strain fundamentally modifies the preferred sliding pathway due to anisotropic expansion of surface electronic state. These results highlight that the functionalized MXenes with strain-controllable frictional properties are promising lubricating materials because of their low sliding energy barrier and excellent mechanical properties.